A portfolio of China's urban water governance sector: administrative system, coordination problems and policy evolution. Issue 4 (3rd July 2020) - Jia, Shaofeng; Li, Dalong; Wang, Raymond Yu
ABSTRACT: Urban water governance in China has received increasing academic and policy attention owing to frequent urban water crises. Drawing on documentary analysis and field investigations, this article analyzes the administrative system and recent policy developments vis-à-vis urban water governance in China. It demonstrates the main problems of, and mechanisms for, interdepartmental and interjurisdictional coordination, and reviews new policy instruments addressing urgent urban water governance issues. The article argues that coordination mechanisms such as the river chief system are promising but their long-term effectiveness remains to be clarified, and more attention should be paid to policy enforcement and market mechanisms.